Corrosion study of laser cladded Ti-6Al-4V alloy in different corrosive environments. (March 2019) - Nabhani, Mohammad; Shoja Razavi, Reza; Barekat, Masoud
Abstract: Laser cladding of Ti-6Al-4V powder on a substrate with the same chemical composition was performed at different laser powers. The effect of laser power on the microstructure and corrosion behavior was then investigated. Electrochemical studies were performed by potentiodynamic polarization tests in different corrosive environments (3.5% NaCl, 2% H2 SO4 and 5% HCl solutions). Microstructural investigation together with phase characterization revealed that laser cladded Ti-6Al-4V coatings were composed of needle-like martensite (ɑ / ) and coaxial hexagonal compact (ɑ) phases. The coatings were crack-free; however, some cavities were observed in the coatings produced at high laser powers. In all three corrosive environments, the coatings showed a more noble corrosion behavior compared to the untreated substrate. The results showed that corrosion potential increases from −410 (mV) to −130 (mV) in NaCl and from −50 (mV) to −20 (mV) in H2 SO4 enviroments but decreases from −60 (mV) to −270 (mV) in HCl solution. Increasing laser power had a positive effect on the corrosion behavior in NaCl and H2 SO4 solutions; however, it had a negative effect on the corrosion behavior in HCl solution. Highlights: Laser cladded Ti-6Al-4V powder on Ti-6Al-4V substrate using a Nd:YAG laser. The effect of the laser cladding process on microstructure was investigated. The corrosion behavior in different solution after laser cladding on Ti-6Al-4V alloy was evaluated.